Readily accessible sp3-rich cyclic hydrazine frameworks exploiting nitrogen fluxionality. Issue 6 (9th January 2020) - Dean, Conor; Rajkumar, Sundaram; Roesner, Stefan; Carson, Nessa; Clarkson, Guy J.; Wills, Martin; Jones, Matthew; Shipman, Michael
Abstract : A high yielding, flexible strategy to hydrazine based chemical libraries is reported. Using a single stereogenic center, good shape diversity and three dimensionality is achieved by exploitation of the fluxional behavior of the two nitrogens. Abstract : Increased molecular complexity correlates with improved chances of success in the drug development process. Here, a strategy for the creation of sp 3 -rich, non-planar heterocyclic scaffolds suitable for drug discovery is described that obviates the need to generate multiple stereogenic centers with independent control. Asymmetric transfer hydrogenation using a tethered Ru-catalyst is used to efficiently produce a range of enantiopure cyclic hydrazine building blocks (up to 99% ee). Iterative C–N functionalization at the two nitrogen atoms of these compounds produces novel hydrazine and hydrazide based chemical libraries. Wide chemical diversification is possible through variation in the hydrazine structure, use of different functionalization chemistries and coupling partners, and controlled engagement of each nitrogen of the hydrazine in turn. Principal Moment of Inertia (PMI) analysis of this small hydrazine library reveals excellent shape diversity and three-dimensionality. NMR and crystallographic studies confirm these frameworks prefer to orient their substituents in three-dimensional space under the control of a single stereogenic center through exploitation of the fluxional behavior of the two nitrogen atoms.